2019
DOI: 10.3102/0002831219892004
|View full text |Cite
|
Sign up to set email alerts
|

“You Were Going to Go to College”: The Role of Chicano Fathers’ Involvement in Chicana Daughters’ College Choice

Abstract: Using pláticas, the sharing of cultural teachings through intimate and informal conversations, this article analyzes our personal college choice processes as Chicanas by examining the impact of being raised by Chicano college-educated fathers. Drawing on two theoretical frameworks, college-conocimiento, a Latinx college choice conceptual framework, and critical raced-gendered epistemologies, we demonstrate how intimate and informal conversations occur within our own Chicana/o daughter-father relationships in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…These concerns are elevated for undocumented families, as the risk of deportation may further dissuade parents and family members from in‐school involvement (Cross et al 2019; Olivos and Mendoza 2009). Hence, without deploying creative partnership strategies, educators may overlook Latinx families and miss opportunities to build on the culturally rooted tactics these families use to bolster their children’s schooling and shape their children’s college‐going mindsets (Auerbach 2004; Espino 2016; Gándara 1995; Garcia and Mireles‐Rios 2020; Knight‐Manuel et al 2019; Patrón 2020).…”
Section: Sacarlos Adelante: Salvadorans and Economic‐based Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…These concerns are elevated for undocumented families, as the risk of deportation may further dissuade parents and family members from in‐school involvement (Cross et al 2019; Olivos and Mendoza 2009). Hence, without deploying creative partnership strategies, educators may overlook Latinx families and miss opportunities to build on the culturally rooted tactics these families use to bolster their children’s schooling and shape their children’s college‐going mindsets (Auerbach 2004; Espino 2016; Gándara 1995; Garcia and Mireles‐Rios 2020; Knight‐Manuel et al 2019; Patrón 2020).…”
Section: Sacarlos Adelante: Salvadorans and Economic‐based Migrationmentioning
confidence: 99%
“…Educators, researchers, and human service providers should harness the narratives of families of color for the wealth of knowledge that can be used to support students in gaining college access (Carey 2016). Assuredly, when crafting interventions, educators would benefit from learning from the culturally rooted narratives of their Latinx students’ college‐educated family members (see Garcia and Mireles‐Rios 2020). Yet, narratives from families with minimal or no overt college knowledge reveal a wealth of untapped lessons and family histories that can inform educators’ practices (Carey 2016; Kiyama 2011; Shapiro 2018; Varghese and Fuentes 2020).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…All these factors contribute to their academic success. However, these studies focus on first-generation college students, and there is a dearth of research on Chicanx/Latinx who are not first-generation college students, and more specifically on parental engagement of these students (Garcia, 2016, 2019; Garcia & Mireles-Rios, 2020; Kouyoumdjianet al, 2017).…”
Section: Chicanas and Higher Educationmentioning
confidence: 99%
“…More research is needed to understand the nuances of how institutional type affects how Chicanx/Latinx who are not first-generation college students persist and complete college. Furthermore, Garcia and Mireles-Rios (2020) used a plática methodology to examine the role of college-educated Chicano fathers’ involvement in their Chicana daughter’s college choice processes. They found that college-educated Chicano fathers offered cultural knowledges that were specific to their race and gender to assist their daughters in navigating institutional racism.…”
Section: Chicanas and Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation